Luxury and modernism : architecture and the object in Germany, 1900-1933 - Schuldenfrei, Robin (Princeton University Press, 2018)
Consumption: Peter Behrens at the AEG and the luxury of technology -- Objectivity: the Werkbund display window and architecture's object -- Capitalism and crisis: the Haus am Horn and the early Bauhaus -- Production/Reproduction: the irreproducibility of the Bauhaus object -- Subjectivity: Mies van der Rohe's materiality and the re-inscribing of modernism's meaning -- Interiority: Mies van der Rohe, auratic space, and the modern city -- Conclusion: luxury's final manifestations.